Alexander Disease: A Leukodystrophy That May Mimic Brain Tumor. (February 2017) - Tavasoli, Ali; Armangue, Thais; Ho, Cheng-Ying; Whitehead, Matthew; Bornhorst, Miriam; Rhee, Jullie; Hwang, Eugene I.; Wells, Elizabeth M.; Packer, Roger; van der Knaap, Marjo S.; Bugiani, Marianna; Vanderver, Adeline
Alexander disease is a leukodystrophy caused by dominant missense mutations in the gene encoding the glial fibrillary acidic protein. Individuals with this disorder often present with a typical neuroradiologic pattern including white matter abnormalities with brainstem involvement, selective contrast enhancement, and structural changes to the basal ganglia/thalamus. In rare cases, focal lesions have been seen and cause concern for primary malignancies. Here the authors present an infant initially diagnosed with a chiasmatic astrocytoma that was later identified as having glial fibrillary acidic protein mutation-confirmed Alexander disease. Pathologic and radiologic considerations that were helpful in arriving at the correct diagnosis are discussed.